Seasonal fluctuations attenuate stimulatory or inhibitory impacts of colonial birds on abundance, structure and diversity of soil biota - Pen-Mouratov, Stanislav; Dayan, Tamar (Frontiers in Microbiology, 2023)
Soil microorganisms and free-living nematodes were investigated in association with the nesting and roosting habitats of the following piscivorous and omnivorous colonial birds: black kite (Milvus migrans), great cormorant (Phalacrocorax carbo), black-crowned night heron (Nycticorax nycticorax) and little egret (Egretta garzetta), in Israel’s Mediterranean region. Abiotic variables, abundance, trophic structure, sex ratio and genus diversity of soil free-living nematodes, and total abundance of bacteria and fungi, were measured during the wet season, following our previous study conducted during the dry season. The observed soil properties were important drivers of soil biota structure. Presence of the most efficient elements for soil organisms, such as phosphorus and nitrogen, was strongly dependent on the diet of the compared piscivorous and omnivorous bird colonies; levels of these nutrients were notably higher in the bird habitats than in their respective control sites during the study period. Ecological indices showed that the different species of colonial birds can have different (stimulatory or inhibitory) impacts on abundance and diversity of the soil biota, affecting the structure of the soil free-living nematode population at the generic, trophic and sexual levels during the wet season. A comparison with results from the dry season illustrated that seasonal fluctuations can change, and even attenuate the effect of bird activity on the abundance, structure and diversity of the soil communities.